The gender background of texture attributes of pork loin. (February 2018) - Aaslyng, Margit D.; Jensen, Henriette; Karlsson, Anders H.
Abstract: The tenderness of pork loins from castrates, entire males and females was quantified with sensory analysis and measurement of instrumental texture during ageing. Furthermore, the effects of intramuscular fat (IMF), collagen content and solubility, hot carcass weights and meat percentages on tenderness were examined. Meat from castrates was significantly (p = 0.043) more tender than meat from entire males and females as assessed by trained sensory panellists. Tenderness scores were positively affected by IMF content (p = 0.008) and hot carcass weight (p < 0.001), but no effect of collagen content and solubility was found. Meat from all three genders had the same tenderisation rate during ageing (two, five, seven and ten days). It is therefore suggested that meat from entire males and females should be aged for longer than meat from castrates to obtain the same level of tenderness.